The Influence of Digital Innovation in the Formation of Students' Morals at SMA Muhammadiyah PK Kotabarat Surakarta - Fajar Fitriansyah; Mohammad Zakki Azani (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2025)
Morality is a fundamental component in shaping students’ character and is influenced by key social environments, particularly the family and the school. In the era of digital transformation, various technological innovations not only support learning processes but also shape students’ behavioral patterns and moral development through their interactions in digital spaces. This study aims to identify the determinants of students’ moral formation and to critically examine the role of digital innovations in constructing their moral values. Employing a qualitative approach with a case study design at SMA Muhammadiyah Special Program Surakarta, data were collected through interviews, observations, and document analysis to map the dynamics of technological influence on student behavior. The findings indicate that digital platforms such as the PK Best Learning web-based application and the E-Learning system contribute to strengthening discipline, responsibility, and learning regularity through structured assignments, progress monitoring, and systematic learning interactions. Nevertheless, uncontrolled digital exposure poses potential risks of behavioral deviation, highlighting the urgency of digital literacy and sustained collaboration between schools and parents as strategic factors in ensuring the internalization of moral values aligned with Islamic educational principles.